2007
DOI: 10.1007/s11269-007-9217-5
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Recharge Assessment for the Kalahari Catchment of North-eastern Namibia and North-western Botswana with a Regional-scale Water Balance Model

Abstract: Groundwater is the only source of drinking water for the inhabitants of the Kalahari. Thus understanding spatial and temporal variations in groundwater recharge is very important and a regional-scale water balance model has therefore been set up for a 209,149 km 2 catchment in north-eastern Namibia and north-western Botswana. The model has a spatial resolution of 1.5×1.5 km, daily model time-steps, and climatic input parameters for 19 years are used. The distributed, GIS-based, process-oriented, physical water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
(16 reference statements)
5
11
0
Order By: Relevance
“…In addition, in our scenario analysis, short-term heavy rainfall with high intensity substantially increased the hillslope subsurface flow. This was consistent with the study by Wanke et al (2008), who found that high rainfall intensity is important for the development of soil water leakage.…”
Section: Interactions Among Precipitation Soil Texture and Land Use supporting
confidence: 93%
See 1 more Smart Citation
“…In addition, in our scenario analysis, short-term heavy rainfall with high intensity substantially increased the hillslope subsurface flow. This was consistent with the study by Wanke et al (2008), who found that high rainfall intensity is important for the development of soil water leakage.…”
Section: Interactions Among Precipitation Soil Texture and Land Use supporting
confidence: 93%
“…This was consistent with the study by Wanke et al . (), who found that high rainfall intensity is important for the development of soil water leakage.…”
Section: Discussionmentioning
confidence: 99%
“…If direct recharge is the most important process, then the chloride mass balance method which is a reliable method can be used and the parameters for this methodology and its determination must be obtained. These parameters are relatively easy to obtain (e.g., Brunner et al, 2004;Wanke et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, numerical models are useful and robust tools to quantify recharge. Precipitation-runoff modeling or sometime referred to as watershed modeling is a surface-water focused approach, which generally yields groundwater recharge estimates as a residual term in the water budget Equation (Wanke et al 2008). These models are usually lumped and provide a single recharge estimate for the entire watershed.…”
Section: Introductionmentioning
confidence: 99%